RECONSTRUCTION OF SOFT TISSUE DEFECTS AROUND KNEE AND PROXIMAL LEG USING PROXIMAL BASED SURAL ARTERY FLAP - Abdul Sattar, Sumaira; Waqas Sami,; Faisal Akhlaq,; Saira Bhutto,; Shiza Mehak Sohail,; Rabeeaa Farrukh, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Soft tissue defects around the knee and proximal leg represent a challenging clinical scenario for plastic and reconstructive surgeons. These defects can arise from a variety of causes, including traumatic injuries, such as crush injuries and road traffic accidents, thermal injuries like burns, and surgical complications such as infection. Objective of the study was to evaluate the success of proximally based sural artery flap for soft tissue defects around the knee and proximal leg in patients presenting to our tertiary care hospital. Methods: This prospective observational study was conducted at the Department of Plastic & Reconstructive Surgery, Civil Hospital, Karachi, Pakistan. The study included patients with soft tissue defects around the knee and proximal leg, excluding those with specific comorbidities, high BMI, or active smoking. Non-probability convenience sampling was employed. After ethical review committee approval and informed consent, if needed wounds were optimized with thorough debridement then patients underwent proximal-based sural artery flap surgery for soft tissue defects around knee and proximal leg. Flap survival and complications were assessed over three to six weeks. Results: The study included 37 patients, with a median age of 30 years. The most frequent cause of defects was road traffic accidents (73%). Of the patients, 73% were male, and 27% were female. The median duration of soft tissue injury was 5 weeks, and the median duration of surgery was 90 minutes. Flap survival was 97.3%, with 28 flaps surviving without any complications. One patient with a 20-year-old chronic defect experienced partial flap failure. Conclusion: The use of the proximally based sural artery flap represents a promising approach for the successful reconstruction of soft tissue defects around the knee and proximal leg.